Hubungan Jenis Lensa Kontak Dan Keterampilan Pemakaian Lensa Kontak Dengan Kejadian Iritasi Mata Di Optik Nurul Pangkalan Balai Tahun 2022 - Fakhrudin, M.; Raflesia, Satria; Purwakib, Sigit (JOURNAL OF HEALTH SCIENCE, 2025)
Contact lenses are thin plastic lenses that are used in the eyes to help treat vision problems, nearsightedness, farsightedness, astigmatism or astigmatism, and old eyes. This study aims to analyze the relationship between the type of contact lenses and contact lens skills with the incidence of irritation at the Nurul Pangkalan Balai Balai Optics in 2022. The number of respondents in the study was 40 respondents. The data was collected using a simple random sampling technique. The results showed that 22 people (55%) experienced irritation and 18 people (45%) did not experience irritation from a total of 40 respondents. In the skills of using contact lenses there were 23 people (57.5%) classified as skilled in using contact lenses and 17 people (42.5%) were unskilled. Meanwhile, 25 respondents (62.5%) used soft contact lenses and 15 respondents (37.5%) used hard contact lenses. The conclusion of this study is that there is a significant relationship between the type of contact lens and contact lens skills with the incidence of irritation.